The efficiency of systemic‐to‐pulmonary shunts in older children with hypoplastic pulmonary arteries. Issue 6 (26th April 2019) - Zhang, Han; Fan, Xiangming; Su, Junwu; Liu, Yinglong; Zhao, Lei; Li, Gang
Abstract: Background: To investigate the effects of systemic‐to‐pulmonary shunts (SPSs) in older children with hypoplastic pulmonary arteries and the factors affecting the development of the pulmonary arteries. Methods: Eighty‐six children (older than 3 years) who received SPSs were retrospectively analyzed. The perioperative parameters, the postoperative diameter of the pulmonary artery were collected, and the factors influencing the growth of the pulmonary arteries after an initial palliative shunt operation were analyzed. Results: Two patients died postoperatively (2.33%), and the pulse oxygen saturation (SpO2 ) increased from 71.70 ± 6.75% preoperatively to 85.20 ± 11.07% at discharge. During the follow‐up period of 56 (10–99) months, 37 patients (43.02%) underwent subsequent procedures, and in the remaining patients, the McGoon ratio was increased from 0.96 ± 0.48 at the surgery to 1.30 ± 0.31 at the final assessment ( P  < 0.05). Univariate analysis indicated that age younger than 5 years old ( P  < 0.05), pulmonary artery forward flow ( P  < 0.05) and a diagnosis of tetralogy of Fallot ( P  < 0.05) played positive roles in the growth of the pulmonary artery after surgery, while children with a McGoon ratio less than 0.6 showed poor development of the pulmonary arteries ( P  < 0.05). Multivariate analysis showed that age younger than 5 years old ( P  < 0.05) and pulmonary artery forward flow ( P  < 0.05) were positive effectors on the growth of the pulmonary artery. Conclusions: Older children with cyanotic congenital heart disease benefited from a systemic‐pulmonary shunt and showed increased postoperative oxygen saturation and development of the pulmonary arteries. Age younger than 5 years and pulmonary artery antegrade flow were the positive factors influencing the growth of the pulmonary arteries postoperatively.